"Public goods" or "diplomatic tools": a framing research on Chinese and American media reports regarding Chinese COVID-19 vaccine. Issue 1 (2nd January 2023) - Ju, Weilun; Sannusi, Shahrul Nazmi; Mohamad, Emma
Abstract: This study aims to conduct a framing analysis of Chinese and American media coverage of Chinese COVID-19 vaccine. Since 2021, China exports or donates vaccines to developing countries, arousing the attention of Chinese and American media. The competition between China and the USA over national image extends to the vaccine field. Media framing is a powerful tool to construct a national image. It is worth comparing how Chinese and American media use framings to construct national images on vaccine issues. This study conducts a framing analysis of news coverage in People's Daily (PD) and The New York Times (NYT) on Chinese COVID-19 vaccine from January to March 2021 to determine how the media use specific framings to construct national images. The results show PD favors official action and cooperation frames, constructing the discourse of "public goods" and "cooperation" and shaping a fair and cooperative China image; while NYT favors official action, conflict and skepticism frames, constructing the discourse of "diplomatic tool" and "competition" and shaping a selfish and competitive China image. A positive image is helpful for China to reposition itself in global public opinion and enhance its soft power, while a negative discourse deconstructs the positive China image and counterbalances China's vaccine diplomacy.